Overnight urinary 11-hydroxycorticosteroid estimations in diagnosis of Cushing's syndrome. Issue 6037 (18th September 1976) - Mattingly, D; Tyler, C
Abstract : Overnight specimens of urine were collected from control, obese, and hirsute women and from 11 women with Cushing's syndrome. Urinary 11-hydroxycorticosteroid levels in the group with Cushing's syndrome were significantly higher than in the other three groups. This simple test has proved invaluable when screening for Cushing's syndrome in a busy outpatient clinic.